2013
DOI: 10.1155/2013/623978
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Heterogeneous Nuclear Ribonucleoproteins in Stem Cell Potency and Differentiation

Abstract: Stem cells possess huge importance in developmental biology, disease modelling, cell replacement therapy, and tissue engineering in regenerative medicine because they have the remarkable potential for self-renewal and to differentiate into almost all the cell types in the human body. Elucidation of molecular mechanisms regulating stem cell potency and differentiation is essential and critical for extensive application. Heterogeneous nuclear ribonucleoproteins (hnRNPs) are modular proteins consisting of RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 118 publications
0
17
0
1
Order By: Relevance
“…hnRNPs are modular proteins consisting of RNA-binding motifs and auxiliary domains characterized by extensive and divergent functions in nucleic acid metabolism. As such, a diverse function of the hnRNPs in gene regulation ranging from nascent transcript packaging to transcriptional regulation, alternative slicing, nucleocytoplasmic transport, and translational regulation of mRNA, has been increasingly reported in the literature25. Importantly, by using nuclear proteomics analyses we observed the two hnRNPs, hnRNPA113 and hnRNPA2B126, are closely regulated during VSMC differentiation from stem cells.…”
Section: Discussionmentioning
confidence: 70%
“…hnRNPs are modular proteins consisting of RNA-binding motifs and auxiliary domains characterized by extensive and divergent functions in nucleic acid metabolism. As such, a diverse function of the hnRNPs in gene regulation ranging from nascent transcript packaging to transcriptional regulation, alternative slicing, nucleocytoplasmic transport, and translational regulation of mRNA, has been increasingly reported in the literature25. Importantly, by using nuclear proteomics analyses we observed the two hnRNPs, hnRNPA113 and hnRNPA2B126, are closely regulated during VSMC differentiation from stem cells.…”
Section: Discussionmentioning
confidence: 70%
“…Studying the role of hnRNPs in cell cycle regulation and cell differentiation has recently opened a new exciting area of investigation (93). Our data together with data present in public data bank (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified heterogeneous nuclear ribonucleoprotein (hnRNP) A1 and hnRNPU as TRA2β4 -binding proteins using biotinylated RNA pull-down and RNA immunoprecipitation assays. The hnRNP family functions as major splicing factors as well as transcriptional regulators for various genes 17 . In fact, both hnRNPA1 and hnRNPU could upregulate the promoter activity of TRA2B .…”
Section: Introductionmentioning
confidence: 99%